The Transformative Impact of Inquiry-Based Learning on EFL Students’ Grammatical Mastery and Learning Engagement: An Experimental Study on Degrees of Comparison - Amiruddin; Zahara A’Lia (Jurnal Pengembangan Profesi Guru dan Dosen, 2025)
This research investigates the efficacy and reception of the Inquiry Learning Strategy (ILS) in an Indonesian English as a Foreign Language (EFL) context, focusing on a specific grammatical structure: the degrees of comparison. It aims to measure the strategy's impact on academic achievement and to comprehensively understand student perceptions regarding its influence on engagement, collaboration, and the overall learning environment. Employing a quantitative pre-experimental design, this study utilized a one-group pretest-posttest model. The participants consisted of 27 eighth-grade students from SMPN 9 Banda Aceh, selected through purposive sampling. Data collection spanned four meetings, integrating a diagnostic pretest, a structured ILS intervention conducted over two sessions, an evaluative posttest, and a detailed Likert-scale questionnaire. Statistical analysis was performed using descriptive statistics and a paired-samples t-test, while questionnaire data were analyzed using percentage-based thematic analysis.The findings demonstrate a statistically significant improvement in grammatical mastery. The mean score increased from 50.37 (SD = 14.54) in the pretest to 77.78 (SD = 12.89) in the posttest, with a t-test confirming significance (t(26) = -13.558, p < .001). Furthermore, questionnaire results revealed overwhelmingly positive student perceptions. Over 96% of respondents agreed ILS facilitated understanding and collaboration, while 63% strongly affirmed it increased their activeness and enthusiasm. The strategy was endorsed as enjoyable, motivating, and highly suitable for EFL learning.